ANALISIS TITIK IMPAS, TINGKAT EFISIENSI DAN TINGKAT KARAKTERISTIK PERTANIAN ORGANIK DI BOYOLALI - SUSWADI SUSWADI (JURNAL ILMIAH AGRINECA, 2018)
Farmers' income levels are generally influenced by many factors. Several factors related to the income level are the factors that come from the society itself, among others, from the socio-economic characteristics of the farmers themselves. Organic rice farming is one of the commodities that have a bright prospect to increase the income of farmers. This can give motivation for farmers to develop organic farming in the hope that harvest will get high yield. The dangers posed by modern agricultural farming systems to health and the environment lead to increased public demand for organic products. The purpose of this research is to (1) This research aims to know and analyze the characteristics of farmers, (2) to analyze the total cost and revenue and income of organic rice, (3) to analyze the efficiency level and BEP (Break Even Point) certified organic paddy farming . Sampling method used in this research is simple random sampling with 40 farmers counted by Slovin formula. The analysis used by: (1) Scale Average analysis for farmer characteristics (2) method of cost analysis and revenue and farming income, and (3) Analysis of farming efficiency using R / C (Return Cost Ratio) analysis method. The location of research is determined by purposive that is Dlingo village, Mojosongo sub-district, Boyolali regency. The results of this study conclude that: (1) Characteristics of organic farmers are men more role than women, age of organic farming business over 50 years, Most farmers in Dlingo village have been living for more than 30 years, the main livelihood farmers is the agricultural sector. (2) Based on the total average total cost for organic farming from certified group on average Rp.20.495.000, - Average revenue of Rp. 35.000.000, -. Income per planting season is Rp. 14505.000, -. The organic certified farmer group earns a R / C ratio of 1.7, indicating that R / C> 1, then the farming with the certified organic system is efficient. Rice farming with certified organic system is advantageous because BEP value of production volume is 2,927 <farmer production, while BEP value is production price 4,099 <selling price at farmer level. Â